Analisis Dampak Produk Domestik Regional Bruto (PDRB) Berdasarkan Harga Konstan Terhadap Pendapatan Masyarakat Kabupaten Bone 2011-2015 - Muhammad Sabil; H. Firdaus H. Firdaus (Jurnal Ilmiah Al-Tsarwah : ilmu ekonomi dan keuangan (konvensional dan syariah), 2018)
This research is to analyze the Impact of Gross Regional Domestic Product (GRDP) Based on Constant Prices on Community Revenues Bone District 2011-2015. In this study, researchers took 3 samples from 17 sectors in Gross Regional Domestic Products at Constant Prices as populations, namely Agriculture, Forestry, and Fisheries. The reason the researchers took these three samples, because in Bone District were the three superior sectors. Data collection methods used through the documentation method. The data taken was analyzed by Simple Lienear Regression with the help of SPSS 16.0 software. with regression expression Y = a + bx. The results of this study indicate that the results of linear regression analysis produce a regression equation Y = 0.984 + 0.372, where the constant (a) is 0.984 and the coefficient of the independent variable (X) is 0.372. Once at GRDP = 0, then Community Revenue has a value of 0.984 and if GRDP (X) experiences a 1% increase, then Community Income (Y), will increase by 0.372 to 1.356 as well if GRDP is at 4% Community Revenue as much as 2.47%. This means that there is a relationship between GDP (X) and Community Income variable (Y) or rejecting the null hypothesis (H0) and accepting the alternative hypothesis (Ha) with a significant level of 0.05 or 5% where Sig. 0.05 or tcount ttable . (Sig. = 0.620 0.05, or 0.551 3.182) and the determinant coefficient of 9.2% or 9%.